Global changes may be promoting a rise in select cyanobacteria in nutrient‐poor northern lakes. (1st July 2020) - Freeman, Erika C.; Creed, Irena F.; Jones, Blake; Bergström, Ann‐Kristin
Abstract: The interacting effects of global changes—including increased temperature, altered precipitation, reduced acidification and increased dissolved organic matter loads to lakes—are anticipated to create favourable environmental conditions for cyanobacteria in northern lakes. However, responses of cyanobacteria to these global changes are complex, if not contradictory. We hypothesized that absolute and relative biovolumes of cyanobacteria (both total and specific genera) are increasing in Swedish nutrient‐poor lakes and that these increases are associated with global changes. We tested these hypotheses using data from 28 nutrient‐poor Swedish lakes over 16 years (1998–2013). Increases in cyanobacteria relative biovolume were identified in 21% of the study sites, primarily in the southeastern region of Sweden, and were composed mostly of increases from three specific genera: Merismopedia, Chroococcus and Dolichospermum . Taxon‐specific changes were related to different environmental stressors; that is, increased surface water temperature favoured higher Merismopedia relative biovolume in low pH lakes with high nitrogen to phosphorus ratios, whereas acidification recovery was statistically related to increased relative biovolumes of Chroococcus and Dolichospermum . In addition, enhanced dissolved organic matter loads were identified as potential determinants of Chroococcus suppression and Dolichospermum promotion. Our findings highlight that specific genera of cyanobacteria benefit from different environmental changes. Our ability to predict the risk of cyanobacteria prevalence requires consideration of the environmental condition of a lake and the sensitivities of the cyanobacteria genera within the lake. Regional patterns may emerge due to spatial autocorrelations within and among lake history, rates and direction of environmental change and the niche space occupied by specific cyanobacteria. Abstract : Most broad‐scale analyses lump cyanobacteria into one single group. Here we provide novel insights by focusing on genera‐specific data for cyanobacteria in northern lakes with a temporally and spatially extensive Swedish dataset. We hypothesized that absolute and relative biovolumes of potentially harmful cyanobacteria are increasing in nutrient‐poor lakes, and that these increases are associated with global atmospheric changes. We found that taxon‐specific changes were related to the interactive effects of climate change and acidification recovery—and that the starting conditions and rates of global changes varied across the country creating environmental niches that favoured different cyanobacteria genera.